2010
DOI: 10.1136/jramc-156-03-07
|View full text |Cite
|
Sign up to set email alerts
|

UK Role 4 Military Infectious Diseases at Birmingham Heartlands Hospital in 2005-9

Abstract: Dermatological infections and undifferentiated febrile illnesses that require management at a UK Role 4 facility are important causes of disease non-battle injury. Prospective collection of this data in the future will be a valuable asset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…For example, leishmaniasis has been diagnosed in American, Canadian, Dutch, and British soldiers returning from active duty in Leishmania-endemic region including Afghanistan and Iraq. 36,37 Furthermore, several cases of leishmaniasis have been reported in people who traveled to endemic areas for business or pleasure. 38 A recent study showed that 6% and 3% of people who traveled to industrialized nations in Europe (including Italy, Spain, and Turkey) and Latin America, respectively, were diagnosed with CL.…”
Section: Opinion: Benefits Of Continued Researchmentioning
confidence: 99%
“…For example, leishmaniasis has been diagnosed in American, Canadian, Dutch, and British soldiers returning from active duty in Leishmania-endemic region including Afghanistan and Iraq. 36,37 Furthermore, several cases of leishmaniasis have been reported in people who traveled to endemic areas for business or pleasure. 38 A recent study showed that 6% and 3% of people who traveled to industrialized nations in Europe (including Italy, Spain, and Turkey) and Latin America, respectively, were diagnosed with CL.…”
Section: Opinion: Benefits Of Continued Researchmentioning
confidence: 99%
“…However, this could probably be done retrospectively and would be worthwhile in view of what the National Audit Office has said about the MOD needing to do more data analysis on this topic 3. Until more detailed figures are available officially, the work of clinicians collecting such data at Role 3 and Role 4 medical facilities1 4 will remain vital and should be fully supported.…”
mentioning
confidence: 99%
“…Infections such as Q fever and bacterial gastroenteritis can also have serious long-term sequelae that are not recognised by current data collection methods. Overall, a wide range of infectious and tropical diseases continue to be seen in British troops overseas and on their return to the UK 57. However, this century has also seen a marked reduction in the facilities and other resources available for military teaching and research on these diseases 58.…”
Section: British Military Experiences In the 21st Centurymentioning
confidence: 99%